Dapagliflozin Prevents Kidney Glycogen Accumulation and Improves Renal Proximal Tubule Cell Functions in a Mouse Model of Glycogen Storage Disease Type 1b. Issue 10 (October 2022) - D'Acierno, Mariavittoria; Resaz, Roberta; Iervolino, Anna; Nielsen, Rikke; Sardella, Donato; Siccardi, Sabrina; Costanzo, Vincenzo; D'Apolito, Luciano; Suzumoto, Yoko; Segalerba, Daniela; Astigiano, Simonetta; Perna, Alessandra F.; et al.
Significance Statement: Glucose homeostasis in proximal tubule cells requires an interplay between transport and metabolic activity. Using a mouse model of inducible G6PT suppression that mimics GSD1b disease, we demonstrate that hexokinase-1 activation and glycogen accumulation are the main causes of proximal tubule dysfunction. In addition, we provide proof of concept for the efficacy of dapagliflozin in preventing glycogen accumulation and, therefore, in restoring proximal tubule morphology and function, opening a new venue to repurpose this drug for treating patients with GSD1b. Visual Abstract: Abstract : Background: Mutations in SLC37A4, which encodes the intracellular glucose transporter G6PT, cause the rare glycogen storage disease type 1b (GSD1b). A long-term consequence of GSD1b is kidney failure, which requires KRT. The main protein markers of proximal tubule function, including NaPi2A, NHE3, SGLT2, GLUT2, and AQP1, are downregulated as part of the disease phenotype. Methods: We utilized an inducible mouse model of GSD1b, TM-G6PT −/−, to show that glycogen accumulation plays a crucial role in altering proximal tubule morphology and function. To limit glucose entry into proximal tubule cells and thus to prevent glycogen accumulation, we administered an SGLT2-inhibitor, dapagliflozin, to TM-G6PT −/− mice. Results: In proximal tubule cells, G6PT suppression stimulates the upregulation and activity of hexokinase-I, which increases availability of the reabsorbed glucose for intracellular metabolism. Dapagliflozin prevented glycogen accumulation and improved kidney morphology by promoting a metabolic switch from glycogen synthesis toward lysis and by restoring expression levels of the main proximal tubule functional markers. Conclusion: We provide proof of concept for the efficacy of dapagliflozin in preserving kidney function in GSD1b mice. Our findings could represent the basis for repurposing this drug to treat patients with GSD1b.